Propriedades físicas, estoque de carbono e produtividade de soja com manejos da aveia preta em sistema de integração lavoura-pecuária - Mattei, Eloisa (2018)
In recent years, integrated production systems have become increasingly expressive in the southern regions of the country, with the introduction of crop-livestock integration system, when conducted and managed in a clear way may be able to promote numerous benefits. Therefore, the objective of this work was to evaluate the effect of seeding technologies of blackbird and fallow in an area cultivated and managed in a crop-livestock integration system, on soil physical and chemical properties, decomposition and nutrient release two in the culture and evaluation of the components of production and production in the culture of soy in succession. The experiment was conducted in the municipality of Marechal Cândido Rondon - PR, in a very clayey eutrophic Red Latosol, using a randomized block design with a control plot, with additional control, with four replications. The doses were composed of two black oats (40 and 60 kg ha-1) sowing densities (range A), plus the fallow and maneuvers of the bird (without collar, one collar and two year of 2016). The total and total organic carbon and nitrogen contents, organic matter, density, macroporosity and microporosity, total porosity and soil resistance to penetration were quantified, and the release of plant nutrients from oats during soybean cultivation in succession. after the winter crop and after the soybean harvest.In the summer, in the 2016/2017 harvest, the soybean crop was implanted, where the principles of the agronomic and productive characteristics were evaluated. with natural resection of forage turnip + ryegrass were the ones that are more fragile as larger dry matter yields. The amount of nutrients, N, P and K released from the residues, were spot s, independent of the adopted management. Potassium was the nutrient released faster from the residues, and the time of fertilization of the crop to be implanted in succession should be considered. The system of crop-livestock integration is not carried out and two grazing of the bird, even so the ground cover allows the cycling of nutrients. Seed density from the booster and/or managements were also not promenuous in COT and ECOT. The use of 40 kg ha-1 of oat seeds is recommended, not promoting change in the addition of MOS. The lowest semifa density is higher by a 10-20 cm layer after a soybean harvest. The sowing density of 40 kg ha-1 associated with non-sticking management presented higher soil density. The crop-livestock integration system and / or the collules promote changes, but do not compromise the physical quality of the soil. The use of 40 kg ha-1 of oat seeds for the western region of Paraná is indicated because it does not promote changes in soybean suction and generate savings in the purchase of seeds. The cultivation of birds is a winter period in a crop-livestock integration system, regardless of the seeding density and management adopted, does not interfere in the productivity of the soybeans grown in sequence, thus being an excellent alternative of diversification of the production of the property.